Nutritional and histopathological studies on Jamunapari goats fed on concentrate diets supple mented with various levels of leucaena leaves - HAQUE, N; KHAN, M Y; LAL, MURARI; PARHAR, N S (The Indian Journal of Animal Sciences, 2013)
Fifteen Jamlmapari male goats, weighing 22.0 kg were divided into 3 groups of 5 animals each. The animals were offered rations containing leaves and twigs of Leucaena leucocephala to provide 0, 25 and 50% of CP of vital ratlons m. L1, L2 and L groups. Three animals from each group were sacrificed after a feeding for 330 days for pathological exammation of Vital organs. Incorporation ofleucaena in L3 group resulted in significant (P<0.05)increase in DM consumption. Except EE, the digestibility of DM, OM, CP, ADF, NDF and cellulose was similar on different treatments. Incorporation of leucaena leaves in diets resulted in reduction of EE digestibility which was 62.7, 56.3 and 42.1 in L1, L2 and L3 groups respectively. The average daily live-weight gain was 39±2.3, 48±4.5 and 45±3.9g per head in L1 L2 and L3 groups with no significant differences (P<0.05). Histopathological examination of vital organs did not reveal any significant change due to leucaena feeding, excepting in thyroid glands and kidneys. The thyroid glands of Ll and L3 revealed mild variation in size of follicles with normal or pale staining colloids. Kidneys revealed intense engorgement of interstitial blood vessels With extravasatIon of red blood corpuscles. It is concluded that ieucaena may be providing up to 50% CP of the ration for goats up to 330 days and it does not cause any serious disorder in vital organs.